Energy intake and expenditure during a 6-day cycling stage race - Rehrer, N. J.; Hellemans, I. J.; Rolleston, A. K.; Rush, E.; Miller, B. F. (Scandinavian Journal of Medicine & Science in Sports, 2010)
Energy intake (EI) and energy expenditure (EE) are relatively easy to measure accurately over short periods in a laboratory setting, but less so during a multi-day competition. Our goal was to measure EI and EE as accurately as possible during a 6-day, 10-stage cycling race. We prepared all meals and supplements, assessed EI (weighed diet-records) and macrontrient intake, total EE (doubly labelled water), resting metabolic rate (respiratory gas exchange), exercise EE (power meters), and body mass. Body composition was measured several days before and after racing (dual x-ray absorptiometry). Body mass remained stable over the course of the race. The mean EI (27.3±3.8 MJ/day) nearly matched EE (27.4±2.0 MJ/day). The majority (62%) of EE was exercise EE. Macronutrient intake was within or exceeded the recommendations. Lean body mass increased and fat mass decreased in most of our participants. Our study indicates that EI can match high EE with adequate macronutrient intake during multi-day cycle racing and may be facilitated by appropriate foods being available at appropriate times. This optimization of nutritional provision supports positive changes in body composition.